Optimal sedation/anesthesia practices for painless gastroscopy in older adults: a randomized trial - Liu, Jing-Zhen; Liu, Xin; Wei, Duan-Gao (Frontiers in Medicine, 2025)
ObjectiveThe aim of this study is to conduct a preliminary exploration of the optimal sedation depth for painless gastroscopy in older adults.MethodsSixty older adults who underwent painless gastroscopy in April 2023 at Northern Jiangsu People’s Hospital, Jiangsu Province, were included in the study and randomly assigned to four groups: minimal sedation (Group I), moderate sedation (Group II), deep sedation (Group III), and anesthesia (Group IV). Data were collected on sedation depth after induction and titration (T1), swallowing response during gastroscope insertion (T2), and bucking during the procedure (T3).ResultsFollowing T1, both systolic blood pressure (SBP) and diastolic blood pressure (DBP) showed a significant decrease, with change rates being notably higher in groups III and IV compared to groups I and II (P < 0.05). The failure rate of gastroscope insertion was significantly higher in groups I and II than in groups III and IV (P < 0.05). At T2, bucking and body movement scores were substantially lower in groups III and IV than in groups I and II (P < 0.05). After T2, the heart rate (HR) change rates in groups III and IV were significantly lower than in groups I and II (P < 0.05). Additionally, SBP and DBP were further reduced, with change rates being markedly higher in groups III and IV compared to groups I and II (P < 0.05). At T3, the incidence of bucking and body movements was significantly lower in groups II, III, and IV than in group I (P < 0.05).ConclusionDeep sedation and anesthesia are more suitable for older adults undergoing painless gastroscopy in terms of sedation depth.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=191819, ChiCTR2300069999.